Teachers’ and Students’ Views on Multidisciplinary Curriculum Implementation in Secondary Education in Anambra and Enugu States - Nkolika, Chukwuka Judith (PT. Pusmedia Group Indonesia, 2026)
Secondary education in Nigeria faces increasing demands to equip students with critical thinking and problem-solving skills necessary for higher education and the workforce. Despite policy efforts to introduce multidisciplinary curricula, challenges persist in effectively implementing these approaches in schools, limiting their potential impact on students’ cognitive development. The study employed a quantitative descriptive survey design with inferential analysis to examine multidisciplinary curriculum implementation in secondary schools in Anambra and Enugu States. A multi-stage sampling technique was used to select 500 students and educators from public and private schools. Data were collected using a validated and reliable structured questionnaire measuring demographic variables, problem-solving skills, educators’ perceived challenges, and students’ perceptions of relevance to critical thinking. Questionnaires were administered directly, with ethical standards observed. Data were analyzed using SPSS, applying descriptive statistics, independent samples t-tests, and simple linear regression at the 0.05 level of significance. The results indicate that multidisciplinary education enhances students’ problem-solving skills in both states, with Anambra students recording higher mean scores in applying knowledge (3.15 vs. 3.03), creativity (3.47 vs. 3.37), decision-making (3.20 vs. 3.12), and real-world problem solving (3.10 vs. 2.99), while Enugu students reported greater confidence in handling complex tasks (2.82 vs. 1.84). Educators in Enugu perceived more serious implementation challenges, especially inadequate training (2.82 vs. 1.84) and curriculum overload (2.66 vs. 1.41), though both states shared similar concerns about assessment methods (3.31). Students generally viewed multidisciplinary education as relevant to critical thinking, with Anambra showing slightly higher engagement (3.47 vs. 3.41) and deeper thinking (3.42 vs. 3.33). Regression analysis revealed a moderate, significant impact on problem-solving skills (R = 0.469; R² = 0.220; p < .001), educators’ challenges significantly influenced implementation (t = –8.238; p < .001), while students’ perceptions were not significantly related to critical thinking (p = .289). The study concludes that multidisciplinary curricula hold substantial potential to enhance students’ cognitive skills, but effective implementation requires targeted teacher training, curriculum adjustments, and improved resource provision. These findings offer guidance for policymakers, school administrators, and curriculum planners aiming to strengthen secondary education outcomes.